Polar stratospheric ice cloud above Spitsbergen - Maturilli, Marion; Dörnbrack, Andreas (Journal of Geophysical Research, 2006)
Within the extremely cold and stable polar vortex of winter 2004–2005 a polar stratospheric ice cloud was observed from Ny-Ålesund (Spitsbergen) on 26 January 2005. The observation of a cloud with backscatter ratios up to 23 and volume depolarization larger than 50% is unique in our 15 year ground-based lidar data record. Simultaneous balloon-borne water vapor measurements indicate the presence of mesoscale ice clouds nearby. Normally, low horizontal wind speeds inside the inner vortex prevent vertical wave propagation. However, the rare coincidence of different meteorological processes occurring during a poleward-breaking Rossby wave event caused favorable conditions for the vertical propagation of mountain waves excited by the flow past Spitsbergen. Detailed meteorological analysis shows that the ice particle formation processes on 26 January 2005 were most likely provoked by mesoscale stratospheric temperature anomalies, leading to a local reduction in water vapor